Students' Perceptions and Learning Needs: A Fundamental Aspect in Designing English Flashcards for Accountants - Acfira, Lukytta Gusti; Ichsan, Hisyam (Universitas Terbuka, 2024)
The study aimed to explore students' perspectives on learning English for accounting and assess the effectiveness of current instructional methods, focusing on the potential benefits of using flashcards as a pedagogical tool. The research involved 20 accounting students from Universitas Sulawesi Barat (Unsulbar), who participated in surveys and semi-structured interviews. Data collection focused on students’ perceptions of the importance and difficulty of English for accounting, the effectiveness of current teaching methods, and their opinions on using flashcards. The study found that accounting students perceive English as crucial yet challenging due to the complexity of specialized terminology. Current teaching methods were deemed insufficient in addressing these challenges, leading to a general agreement on the potential benefits of flashcards. The results indicate that flashcards significantly improve students’ motivation and retention of accounting terms by providing interactive and visually engaging learning opportunities. The research highlights that incorporating flashcards into English for Specific Purposes (ESP) can address the unique needs of non-English major students and enhance their understanding of field-specific vocabulary. This study contributes to the field of educational research by demonstrating the practical application of flashcards in specialized vocabulary learning and offering insights into effective instructional strategies for non-English major students. The findings suggest that future research should further explore diverse flashcard designs and long-term impacts on language proficiency.